1991
DOI: 10.1111/j.1439-0450.1991.tb00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Rhodococcus equi Isolated from Submaxillary Lymph Nodes of Pigs in Japan

Abstract: Summary Isolation of Rhodococcus equi from the submaxillary lymph nodes of pigs, with or without caseous lymphadenitis, and typing of the isolates by two serological methods were carried out. The rate of isolation of the organisms from the lymph nodes of pigs was 5 times higher in the lymph nodes with caseous lymphadenitis than in those without the lesion. Of 219 isolates, 146 (66.7%) were typable by the method of Prescott, while all the 219 isolates (100 %) were typable by the method of Nakazawa et al. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…The studies on this topic report conflicting results: some authors recovered R. equi from the lymph nodes of healthy pigs (Takai et al, 1996;Madarame et al, 1998;Dvorska et al, 1999;Makrai et al, 2005) while others reported the isolation of R. equi almost exclusively from lymph nodes with granulomatous lesions, identifying it as the causative agent of lymphadenitis in pigs (Komijn et al, 2007). In the scope of one study, R. equi was found in pigs with and without caseous lymphadenitis, but the isolation rate was reported to be five times higher in the lymph nodes with lesions (Katsumi et al, 1991). In our previous study (Pate et al, 2004) R. equi was isolated from swine lymph nodes with lesions alone (27.3%), or together with mycobacteria (5.4%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The studies on this topic report conflicting results: some authors recovered R. equi from the lymph nodes of healthy pigs (Takai et al, 1996;Madarame et al, 1998;Dvorska et al, 1999;Makrai et al, 2005) while others reported the isolation of R. equi almost exclusively from lymph nodes with granulomatous lesions, identifying it as the causative agent of lymphadenitis in pigs (Komijn et al, 2007). In the scope of one study, R. equi was found in pigs with and without caseous lymphadenitis, but the isolation rate was reported to be five times higher in the lymph nodes with lesions (Katsumi et al, 1991). In our previous study (Pate et al, 2004) R. equi was isolated from swine lymph nodes with lesions alone (27.3%), or together with mycobacteria (5.4%).…”
Section: Discussionmentioning
confidence: 97%
“…Infection can also occur in a wide variety of other mammals, usually due to immunosuppression (Prescott, 1991). R. equi is frequently isolated from the lymph nodes of pigs (Barton and Hughes, 1980;Katsumi et al, 1991;Prescott, 1991;Takai et al, 1996;Pate et al, 2004;Makrai et al, 2005;Shitaye et al, 2006;Komijn et al, 2007); it also seems to be gaining importance in human health (Jones et al, 1989;Kedlaya et al, 2001;Weinstock and Brown, 2002;Torres-Tortosa et al, 2003;Ulivieri and Oliveri, 2006). Increased numbers of human R. equi infections might be a consequence of the AIDS epidemic but may also reflect the increasing awareness of this opportunistic pathogen (Prescott, 1991).…”
mentioning
confidence: 99%
“…These results suggest that R. equi is widespread in the population of wild boars in Japan, as is the case for domestic pigs in Japan (Takai and Tsubaki, 1985;Katsumi et al, 1991;Takai et al, 1996;Fukunaga et al, 1999). The reason for the higher incidence of R. equi among wild boars than among domestic pigs may be that the former have more frequent contact with soil than domesticated pigs, and R. equi is widespread in the soil (Takai, 1997).…”
mentioning
confidence: 85%
“…In addition to its virulence for foals, R. equi seems also to be an important pathogen to immunocompromised humans, such as organ transplant and AIDS patients (21). R. equi is also common in the submaxillary lymph nodes of pigs (2,8,15,25,27). Katsumi and others (8) isolated R. equi from 45.6% of the submaxillary lymph nodes of swine with lesions and from 9.4% of lymph nodes of swine without lesions.…”
mentioning
confidence: 99%
“…Beside common antigens, several different ones have been found to react in the above-named tests; the results of the two serotyping systems do not completely agree (9). When the Prescott system is used, serotype 2 is the predominating serotype of R. equi isolated from submaxillary lymph nodes of swine (8,9,12).…”
mentioning
confidence: 99%